The Cultural Differences and Intercultural Adaptation on Partnership Relation of Core-Plasma Plantation in Tea Estate of Indonesia - Ninik Sri Rejeki (The Indonesian Journal of Communication Studies, 2009)
This research was a qualitative research aiming at understanding the cultural differences and intercultural adaptation on partnership relation of core-plasma plantation in Tea Estate of Pagilaran Ltd Co, Indonesia. Collecting data were done by depth interviewing the worker’s core plantation and the plasma farmer concerning problems faced by both relationship. The results showed that culture of core plantation community tended to orientate to economical aspect with commercial basis, meanwhile culture of the farmers tended to orientate to group’s interest and to keep on their relationship among them with traditional habit and ecological sound. In relation to adaptation process, the two communities seemed to develop similar culture with capital interest. In this regards the similar cultures can be seen in two sides: from the side of core plantation, people working in the core plantation are come from similar culture with the indigenous farmers and the factory is also located in the farmer’s area. Meanwhile from the point of view of farmers, the similar culture as the result of cultural adaptation. Furthermore, the cultural differences shown by the core plantation and plasma farmer communities were due to the normative rules maintained by the company and also due to the different educational level and knowledge of both. To that respect, in core plantation community, the culture orientated to capital achievement implies the communication attitude on the business interest, where as the communication attitude of farmer community is more orientated to local interest using informal and interpersonal channel. Finally the communication differences in the two communities impede the process of organizational objective. And the communication attitude of the core plantation community is changed and unified with the communication attitude of plasma farmer.